Correctness and algorithmic efficiency of a method for systems genetics - Yap,Jan Michael (Philippine computing journal)
In systems biology and genetics, data integration is a key task towards providing a multi perspective analysis of biological phenomenon. To validate algorithms developed for such purposes, empirical testing is usually done. Theoretical analysis of the algorithm would further highlight properties of a method. In this paper, a method for integrating genetic marker, quantitative trait loci (QTL), phenotypic, and gene sequence data to identify candidate genes causal to a trait is analyzed for algorithmic effectivity and efficiency. Results of the analysis prove the correctness of the method. Additionally, the results show that the method has time complexity O(ng(m+g)), while the space complexity is O(n(m+g+q)), where n is the number of individuals, g is the number of genes, m is the number of markers used as input, and q is the number of quantitative trait loci associated with the trait.